MUHAMMAD ABDUH’S CONCEPT OF MODERNIZATION ISLAMIC EDUCATION - pane, astrianasitoruspane; Eva Dewi; Sutarmo (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2025)
Islamic education plays a crucial role in instilling the values of Islamic teachings within the educational sphere. This study aims to analyze and describe Islamic educational thought from the perspective of Muhammad Abduh. The research employs a library-based approach, using data collection techniques such as documentation from books, scholarly journal articles, and other documents relevant to the research theme. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The findings indicate that Muhammad Abduh was a prominent modern Islamic thinker who initiated various reforms, particularly in the areas of social and political education for Muslims, who at the time were experiencing stagnation. This stagnation was largely due to the influence of jumud—a rigid, unchanging mindset—that Abduh viewed as a form of ignorance. According to him, the Qur’an contains numerous verses that encourage Muslims to think critically, as it is through thinking that knowledge is born. He also supported the views of some Western writers who argued that the decline of the Muslim world was caused by the ideology of jabariyyah (fatalism). To address this, Abduh reformed the education system, including its curriculum and goals. He believed that the traditional education model widely applied in many institutions needed renewal, starting with the education system at Al-Azhar, which he considered the center of Islamic education globally.